EFFECT OF EPINEPHRINE ADMINISTRATION ON MYOCARDIAL REMODELING IN EXPERIMENTAL STUDY - V. R. Veber; S. V. Zhmailova; M. P. Rubanova; P. M. Gubskaya (Рациональная фармакотерапия в кардиологии, 2017)
Aim. To study structural changes in the myocardium of Wistar rats after a single administration of epinephrine.Material and methods. Structural changes in male Wistar rat’s left (LV) and right (RV) ventricle myocardium after a single injection of epinephrine were studied.Results. The density of extracellular spaces in bothLV and RV myocardium increases first after single epinephrine injection (after 2 hours), and then-decreases below reference values in the next control points. It remains so even after 1 month after a single injection of epinephrine in both theLV (3.95±0.64-vs 6.83±0.30 vol% in the control group; p<0.05) and RV (4.71±0.55 vs 6.09±0.33 vol% in the control group; p<0.05). The density of collagen-fibers in both ventricles increases in all the control points, and more significantly in the RV than in theLV after 2 and 24 hours. After 2 hours the density-of collagen fibers in the RV was 25.8±1.39 vs 19.85±1.50 vol% in theLV (p<0.05), and after 24 hours it is 1.5 times higher – 30.47±1.98 vs-18.47±1.27 vol%, respectively, (p<0.05). The cardiomyocytes density in both ventricles decreases considerably without reaching control values even-in 1 month after a single injection of epinephrine.Conclusion. Severe structural changes develop after single administration of epinephrine in both ventricles rat’s myocardium within 2 hours and persist during the first day. At that structural remodeling of theLV and RV ventricles is asynchronous. Complete regression of morphological changes in the myocardium bothLV and RV does not occur even after 1 month after a single injection of epinephrine. The high values of collagen fibers density, that are observed in both ventricles in acute adrenergic stress model, make it possible to assume that single administration of epinephrine triggers myocardial fibrogenesis mechanisms, which are continuing despite the cessation of drug exposure.